Long‐term efficacy and safety of erenumab in migraine prevention: Results from a 5‐year, open‐label treatment phase of a randomized clinical trial - Ashina, Messoud; Goadsby, Peter J.; Reuter, Uwe; Silberstein, Stephen; Dodick, David W.; Xue, Fei; Zhang, Feng; Paiva da Silva Lima, Gabriel; Cheng, Sunfa; Mikol, Daniel D. (European journal of neurology, 2021)
Background and purpose Although erenumab has demonstrated significant reduction in migraine frequency and improved quality of life in studies lasting 3 to 12 months, little is known about long‐term therapy. Methods This study was an open‐label, 5‐year treatment phase following a 12‐week, double‐blind, placebo‐controlled trial in adults with episodic migraine. Patients initially received open‐label erenumab 70 mg, which increased to 140 mg following a protocol amendment. Efficacy analyses included change from baseline in monthly migraine days (MMDs), monthly acute migraine‐specific medication (AMSM) days, and health‐related quality of life. Results Of 383 patients enrolled, 250 switched to 140 mg; 215 (56.1%) completed open‐label treatment. Mean (standard error) change in MMDs from baseline of 8.7 (0.2) days was −5.3 (0.3) days; an average reduction of 62.3% at year 5. Among patients using AMSM at baseline (6.3 [2.8] treatment days), mean change in monthly AMSM days was −4.4 (0.3) days at the end of 5 years. Patient‐reported outcomes indicated stable improvements in disability, headache impact, and migraine‐specific quality of life. Exposure‐adjusted patient incidence rates of adverse events (AEs) were 123.0/100 patient‐years; AEs were most frequently nasopharyngitis, upper respiratory tract infection, and influenza. Serious AEs (SAEs) reported by 49 patients (3.8/100 patient‐years) were mostly single occurrence. Two fatal adverse events were reported. There were no increases in incidence of AEs, SAEs, or AEs leading to treatment discontinuation over 5 years of exposure. Conclusions Treatment with erenumab was associated with reductions in migraine frequency and improvements in health‐related quality of life that were maintained for at least 5 years. No new safety signals were observed. In this 5‐year open‐label treatment phase of erenumab in adult patients with episodic migraine, there was sustained efficacy including reductions in migraine frequency and monthly acute migraine‐specific medication use. At year 5, monthly migraine days were reduced by 5.3 days from baseline (8.7 days), an average reduction of 62.3%, and monthly acute migraine‐specific medication use was reduced 4.4 days from baseline (6.2 days) among patients using acute migraine‐specific medication. No new safety signals were detected over the 5‐year extended treatment period.